Uptake and effect of radioiodine exposure on SKBR-3 cell lines - Miftah Irramah; Yulia Kurniawati; VY Susilo; S Setiyowati; Aisyah Elliyanti (Majalah Kedokteran Andalas, 2020)
Radioiodine has been known as an adjuvant therapy for thyroid cancer. Beside for thyroid cell, radioiodine is reported to be taken up by breast cell. It may be proposed as an alternative for breast cancer therapy. Objective: The study aim was to analyze an uptake of radioiodine and cell proliferation rate of breast cancer cell after the exposure of radioiodine. Methods: This study used SKBR-3 cell line as representative of Human Epidermal Growth Factor Receptor (HER2+) subtype. The cells were planted in DMEM medium added 10% fetal bovine serum (FBS), panstrep 1% and amphotericin B. The cells were grown until 80% confluent and then stripped. Subsequently the cells were sub-cultured on plates 12 and 6 wells respectively for measured uptake of radioiodine and cell proliferation rate after the exposure. Radioiodine uptake was calculated by sum efflux of 125 Iodine (125I) and the amount of uptake after the addition of 95% ethanol. Cell proliferation rate was measured by calculated by using clonogenic assay after iodine-131 (131I) exposure. Results: The average of iodine uptake was 194±50 cpm/106 cell. The average cell proliferation after radioiodine exposure was 54%±5%; Conclusions: Radioiodine is taken by SKBR-3 cells and it reduced cell proliferation rate. This finding shows an opportunity for radioiodine as an alternative therapy for breast cancer. Another studies are needed to understand of cell death the mechanism.